2011
DOI: 10.1021/am200854r
|View full text |Cite
|
Sign up to set email alerts
|

Micro and Nano-Texturization of Intermetallic Oxide Alloys by a Single Anodization Step: Preparation of Artificial Self-Cleaning Surfaces

Abstract: Micro- and nanostructures of Ti-γCu (γ = 0, 30, 50, 70, and 100 wt %) intermetallic alloys were produced through a single anodization step. It was found that the original alloy composition influences the final oxide morphology obtained after anodization which presented formation of a microstructure with nanotubes, nanoparticles or nanopillars on the surface. Pure Ti and Cu oxide metals and their alloys presented hydrophilic or superhydrophilic properties immediately after anodization. When the anodized pure me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…As a result of the morphology study (SEM and profilometer), the explanation of the differences found in CAH of the prepared superhydrophobic PP samples has to be chemical in origin. Recent works carried out in our laboratory on superhydrophobic surfaces have arrived to the conclusion that chemical heterogeneity of the surface is highly important in determining contact-angle hysteresis [45][46][47]. In an attempt to understand the differences in the dynamic component of the superhydrophobic surfaces prepared, surface chemical composition data were obtained by FTIR-ATR and XPS measurements.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of the morphology study (SEM and profilometer), the explanation of the differences found in CAH of the prepared superhydrophobic PP samples has to be chemical in origin. Recent works carried out in our laboratory on superhydrophobic surfaces have arrived to the conclusion that chemical heterogeneity of the surface is highly important in determining contact-angle hysteresis [45][46][47]. In an attempt to understand the differences in the dynamic component of the superhydrophobic surfaces prepared, surface chemical composition data were obtained by FTIR-ATR and XPS measurements.…”
Section: Resultsmentioning
confidence: 99%
“…Surfaces with high Ti-OH concentrations will increase the work of adhesion and their CAHs. Our previous chemical studies on superhydrophobic surfaces also showed that the chemical heterogeneity on the surface strongly influences the final dynamic properties of a superhydrophobic surface [22,[45][46][47].…”
Section: Resultsmentioning
confidence: 99%
“…[47][48][49] After anodisation, the TiO 2 NTs were annealed at 400 °C for 3 h in air atmosphere in order to crystallise the oxide nanotubes layer. The nanotube structures were characterised by scanning electron microscopy (SEM) obtained with EVO50-Carl Zeiss equipment.…”
Section: Methodsmentioning
confidence: 99%
“…As in previous works, 14,16 the PTFE layer, with thickness around 120 nm, was deposited by thermal physical vapor deposition at a base pressure of 2 × 10 −6 Torr. A quartz microbalance monitor was used for thickness control.…”
Section: Methodsmentioning
confidence: 99%